The Teacher's Competence - an Attempt at Synthesis (Original Project) - Dorota Pankowska (Maria Curie-Skłodowska University, Lublin, Poland, 2017)
The article is an attempt at synthesis of different approaches to the teacher's professional competence. The author surveys selected typologies, singling out criteria of the division of competence. Then she proposes a multidimentional presentation of the structure of competence in the form of "competence diagram", and points out the possibilities of its practical use as a tool in planning and evaluating the teachers' training and their individual development, as well as in pedeutological research.